Six autobiographical interludes | Six performative whispers. Plots that sense pedagogies of vital gestures (Praxis Educativa, 2021)
The article recovers, from the narrated life itself, a narrative identity and a condition of intimacy in autobiographical terms, the self-enactment of what I call “the cultivation of some gestures” that speak about how I learned the trade of accompaniment in the direction of thesis. This narrated life shows an ontopolitical and aesthetic position with respect to the meanings given to the investigation and, in this particular case, the director's place of accompaniment. That life narrated in terms of socialities, temporalities and territorialities senses moments and discontinuities marked as forms that we need to make the world more livable and reveal, not only the job, but also the position of being-being-in-the-world. Those scales that involve components of (un) known worlds link these little stories with the great stories. In this paper, I will present six autobiographical interludes that operate as sentimentalists, as performative whispers that allow us to find vital links that define pedagogies of gestures in the process of accompaniment and doctoral training. I will present six autobiographical (dis) continuities as narrative interludes to later co-compose uncomfortable whispers as sentient subjects that we are, as a movement that de-composes not only the pedagogical field, but also that of experience in aesthetic, ethical and political terms.
Keywords: autobiographic research; narrative; pedagogies of vital gestures; accompaniment; performativity